P–098 Use of Dimethylxanthine Theophylline in surgical retrieved sperms that do not recover motility after thawing. (6th August 2021) - Calza, N; Ciotti, P M; Tranquillo, M L; Notarangelo, L; Zuffa, S; Damiano, G; Cipriani, L; Dirodi, M; Franceschelli, A; Porcu, E
Abstract: Study question: Can the use of Theophylline recover motility of frozen surgically retrieved sperms in case of absence of motility after thawing? Summary answer: Theophylline allows to recover motility of thawed surgically retrieved sperms. The utilization of sperms with or without pharmacological activation gives comparable clinical outcomes. What is known already: Testicular sperm motility is usually poor. A method is needed to detect viable sperm for ICSI when motility is totally absent after freezing/thawing. Hypo-osmotic swelling test, mechanical touch technique, laser-assisted immotile sperm selection, birefringence-polarization microscopy and exposure to pharmacological stimulation are techniques used for this purpose. Among pharmacological agents Dimethylxanthine Theophylline is a phosphodiesterase inibitor that improves sperm motility by promoting an increase in intracellular cyclic AMP levels. Few studies report that it is efficient for recovery of sperm motility in cases of thawed testicular and retrograde ejaculation samples improving reproductive outcomes. Study design, size, duration: Retrospective analysis of sixty frozen surgical sperm cycles (45 patients) utilized from February 2018 to November 2020. After thawing, samples were divided in two Groups according to motility recovery. Group A: presence of motility, Group B: absence of motility. Group B was treated with Theophilline and motility was re-assessed after incubation. Activated sperms were utilized for ICSI when available. Sperm motility recovery, fertilization, pregnancy rate/transfer, implantation and miscarriage rate were evaluated in both Groups. Participants/materials, setting, methods: Surgical specimens were treated and concentrated in SpermRinse™ Medium (Vitrolife) and then cryopreservated in nitrogen vapor in TEST Yolk Buffer (Irvine Scientific). After thawing, only samples with no motility recovery were treated with a brief incubation in Theophylline (GM501 SpermMobil, Gynemed) and washed in Polyvinylpyrrolidone (ICSI TM Vitrolife) before injection. ICSI was performed in all cases approximately 4–5 hours after sperm thawing. After fertilization check, transfer was scheduled in day 2. Main results and the role of chance: Women's age Group A (34, 39±2, 29 M±SD) and group B (35, 87±4, 34 M±SD) and men's age Group A (37, 31±5, 12 M±SD) and group B (40, 89±8.15 M±SD) were not significantly different (P= .328 and P=.218) respectively. Group A: 13/60 cycles (21.7%) (9 patients). Pre freezing and post thawing total motility percentage were 34.0±19.0 (M±SD) and 13.5±15.6 (M±SD) respectively (39.8% recovery). Group B: 47/60 cycles (78.3%) (36 patients). Pre freezing total motility percentage was 5.3±8.5 (M±SD) and no motility was recovered post thawing (0%). After treatment with Theophylline total motility was 1.8±1.8 (M±SD) (33.5% recovery). Motile sperms were utilized in all cases except from two in the Group B. Number of injected oocytes was 2.8±1.1 (M±SD) in Group A and 4.3±3.1 (M±SD) in Group B (P=.004) respectively. Fertilisation rate (63.1% and 45.4%, P=.066), Number of embryos transferred (1.8±0.7 M±SD and 1.6±0.7 M±SD, P=.271), Pregnancy rate/Transfer (54.5% and 37.1%, P=.502), Implantation rate (30.0% and 27.8%, P=.919) and Miscarriage rate (33.3% and 30.7%, P=.675) were not statistically significant between Group A and B respectively. In the two cases of group B injected with immotile sperm, fertilization rate was 0% (0/3) and 50% (2/4). Limitations, reasons for caution: A larger study is needed to investigate the recovery of sperms motility (and/or their activation) and clinical outcomes, in particular referring to the origin of sampling (epididymal aspirate and testicular tissue) and type of azoospermia (obstructive and non-obstructive). Wider implications of the findings: Theophylline is an effective tool for sperm motility recovery after thawing allowing to inject viable sperm and facilitating laboratory handling. Trial registration number: Not applicable